Bond strength of individual carbon nanotubes grown directly on carbon fibers. (1st September 2016) - Kim, Kyoung Ju; Lee, Geunsung; Kim, Sung-Dae; Kim, Seong-Il; Youk, Ji Ho; Lee, Jinyong; Kim, Young-Woon; Yu, Woong-Ryeol
Abstract: The performance of carbon nanotube (CNT)-based devices strongly depends on the adhesion of CNTs to the substrate on which they were directly grown. We report on the bond strength of CNTs grown on a carbon fiber (T700SC Toray), measured via in situ pulling of individual CNTs inside a transmission electron microscope. The bond strength of an individual CNT, obtained from the measured pulling force and CNT cross-section, was very high (∼200 MPa), 8–10 times higher than that of an adhesion model assuming only van der Waals interactions (25 MPa), presumably due to carbon–carbon interactions between the CNT (its bottom atoms) and the carbon substrate.